2013
DOI: 10.1155/2013/351810
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Drug‐Loaded Poly(ε‐caprolactone)/Silica Hybrid Nanofibrous Scaffolds

Abstract: We produced drug-loaded poly(ε-caprolactone) (PCL)/silica hybrid nanofibrous scaffolds with various silica sol contents (0 vol%, 10 vol%, 15 vol%, and 20 vol%) using electrospinning and examined their physicochemical properties, mechanical properties, drug release behavior, andin vitrobiocompatibility to evaluate their potential application for guided bone regeneration (GBR). The loading efficiency of tetracycline hydrochloride (TCH) drug was remarkably enhanced by hybridizing the PCL solution with the silica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…As a result, the fiber diameter also decreased to values of 583 ± 112 nm. Similarly, Shin et al (2013) reported that the diameter of electrospun PCL nanofibers containing SiO2 microparticles decreased with the filler content increased.…”
Section: Morphology Of Electrospun Fibersmentioning
confidence: 80%
“…As a result, the fiber diameter also decreased to values of 583 ± 112 nm. Similarly, Shin et al (2013) reported that the diameter of electrospun PCL nanofibers containing SiO2 microparticles decreased with the filler content increased.…”
Section: Morphology Of Electrospun Fibersmentioning
confidence: 80%
“…Some examples are polyphosphazene‐metal oxide (Ti, Al, Si and Zr), silica‐PDMAAm and silica‐PVP composites, shown in Figure . Class 1 hybrids comprising PVA, PCL, PEG, gelatin or chitosan as organic phase show good electro‐spinnability at low temperature that makes them very suitable for the incorporation and controlled delivery of biomolecules (drugs, growth factors) by preserving them from denaturation and degradation …”
Section: Hybrid Sol‐gel Materialsmentioning
confidence: 99%
“…Typically, the polymer is “mechanically” entrapped in the silica network during condensation, and the inorganic and organic chains are held together by H-bonding to the Si–OH surface groups. Biocompatible and degradable polymers of natural and synthetic origin have been used for biomedical applications, such as poly(vinyl alcohol) (PVA) [ 81 , 82 ], PCL [ 83 , 84 ], gelatin [ 85 ] and chitosan [ 86 , 87 , 88 ].…”
Section: Beyond Multiphasic Composite Materials: Hybrid Systemsmentioning
confidence: 99%